Emerging Paradigm of Water Development and Management - Gleick, Peter H. (Water Nepal, 2004)
The language of water is the language of love. Water is not only a resource to be used but also something sacred and pure. Simply put, water is a substance of value to all of us. Whatever differences in cultures, background, perspective and experience, there is a strong commonality about how people view water. As a result, the challenges water management all over the world face are often similar in many ways. I would like to discuss the paradigm we live in, the water beliefs surrounding us in the 20th Century, how the beliefs presented us with particular challenges, how beliefs are changing today and the opportunities that these changes present. Water Nepal Vol.11, No.1, 2004, pp.7-11